Occupational safety and health practice: a study at quarry site by using hirarc form - Tan, Jedidiah; Oh, Kar Heng; Dhat run @ Chat run, Virakphon; Khalid, Amir; Jaat, Norrizam (Penerbit UTHM, 2020)
Occupational Safety and Health Act (OSHA) is a discipline with wide scope involving many specialized fields. In other words, occupational health and safety comprises of aspects in terms of social, mental and physical. This study focuses on the occupational safety and health act ABC Quarry Site located in Kedah. Nowadays, the workers lack of safety and health practice from their companies based on the observations being done one site during this project’s site visit. It is very important for the employers to manage occupational safety and health at the workplace because of the lack of management control often leads to the existence of causes of accidents and allows for unsafe practices among the workers. The data collection was carried out through site investigation and HIRARC form and interview with the person in charge during the site visit. The objective of this study is to promote the occupational environment adaptable to the employer and employees at the workplace based on the existing potential hazard. This report was conducted to identify the hazard on the construction site and to analyse the occupational safety and health in the workplace. This study suggests recommendations for improving occupational safety and health act in the construction site. Effective job safety and health training will help to reduce worker injuries and illnesses.